A influência da complexidade e cor do ambiente sobre o comportamento de emergência e seleção de habitat em Odonata - Tavares, Rafael Israel Santos (Universidade Federal de São Carlos, 2018)
Understanding which behavioral traits influence animal occupation in different habitats is indispensable for understanding ecological processes. Different habitat characteristics, such as the visual complexity of the environment, the presence of three-dimensional structures, the risk of predation and the background color patterns, can act as selective pressures on animal behavior and influence habitat selection and life-cycles. The present dissertation sought to unravel how Odonata larvae behave in different types of microhabitat in controlled trials. In the first chapter, we tested the hypothesis that the larvae select microhabitats, analyzing the preference for environments with low or high complexity, and for light or dark habitats in five laboratory experiments. The results suggest that Odonata larvae show preference for darker microhabitats, regardless of the risk of predation or shelter availability. In addition, the level of visual complexity of the microhabitat may also have influence on habitat selection. In the second chapter, we tested the hypothesis that habitat complexity predicts emergence and mortality rates in Coenagrionidae (Zygoptera) larvae in a system of aquaria complemented with three-dimensional structures to simulate habitats with greater and lesser environmental complexity. The results show that habitats with higher complexity may increase larval emergence rates and reduce mortality rates, highlighting the importance of habitat complexity as one of the favorable conditions for population dynamics. This dissertation adds evidence to the literature on how habitat structure can favor taxa with certain behaviors and strategies of habitat selection, making it possible to unravel ecological questions on population dynamics, dispersion, occurrence and distribution over spatial and temporal scales of aquatic insects communities.
Keywords: Ecologia comportamental; Biodiversidade; Libélulas; Donzelinhas; Comportamento animal; Ecologia aquática; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS